Question-73

Question-73

Find f (2),  f(3), f(4), and  f(5) if f is defined recursively by f(0) = -1,  f(1) = 2, and for n = 1, 2, …

a)     f (n + 1) = f (n) + 4f (n -1).

f (2) = ?

f (3) = ?

f (4) = ?

f (5) = ?

 

b)    f(n + 1) = f(n)^{2} f(n – 1)

f (2) = ?

f (3) = ?

f (4) = ?

f (5) = ?

 

c)     f(n+ 1) = 3f(n)^{2} – 5f(n-1)^{2}

f(2) = ?

(3) =  ?

f(4) = ?

 

Solution

a)f (2) = -2

f (3) = 6

f (4) = -2

f (5) = 22

 

b) f (2) = -4

f (3) = 32

f (4) = -4096

f (5) = 536870912

 

c)  f(2) = 7

(3) = 127

f(4) = 48142

 

Leave a Reply